(untitled) (مجلة البحوث الأكاديمية, 2018)
تهدف هذه الدراسة إلى معرفة مدى تطبيق عوامل ادارة مخاطر السيولة في المصارف التجارية الليبية وفق اسهامات لجنة بازل ، من خلال دراسة ميدانية على المصارف التجارية الليبية بمدينة بنغازي ، وتوصلت الدراسة إلى أن البنوك التجارية الليبية في مدينة بنغازي تطبق العوامل الأساسية لإدارة مخاطر السيولة المتمثلة في الإفصاح العام ، وحجم الودائع ،وأدوات القياس المحاسبي، والإشراف والرقابة ، وأوصت الدراسة بالتأكيد على ضرورة اعتماد اطار عام لإدارة مخاطر السيولة، ، وتحديد مستوى المخاطر المرغوب به ، وتفعيل دور مجالس الإدارة في هذا المجال ، وأوصت أيضاً بإجراء المزيد من الدراسات التي لها علاقة بموضوع مخاطر السيولة. The current study aims to identify the extent that Libyan commercial banks implement the best-accepted banking practices of managing liquidity risk. This will be pursued through recognizing the factors suggested by Basil Committee concerning managing liquidity risk. The study concluded that Libyan commercial banks within Benghazi city apply the basic factors of managing liquidity risk represented in the general disclosure, size of deposits, Accounting Measurement Instruments, supervision, and control. The study emphasize the importance of managing liquidity risk through adopting general internal framework to develop a strategy and practice of such management. It also recommends undertaking further studies on the subject matter.